Comparison of environmental flow assessment methods with a case study on a runoff river-type hydropower plant using hydrological methods - Karakoyun, Yakup; Donmez, Aydin Haci; Yumurtaci, Zehra (SPRINGER, 2018)
This paper focuses on the environmental flow assessment (EFA) methods that maintain the river ecosystem and its integrity for hydropower plants (HPP) with their implementations on a run-off river type HPP. EFA is a crucial phenomenon in terms of electricity production and sustaining river integrity simultaneously. The novelty of this study is that it consists both a comparison of widely used preferred EFA methods and a detailed investigation of the river with pre and post-dam flow regimes. The research shows that by expanding the content and scope of the methods, their relative reliabilities increase. However, this situation requires much more expert, money, and time. Apart from most of the relevant literature, pre and post-dam situations are investigated with a flow duration curve (FDC). It is concluded that the dramatic difference between the flow characteristics of pre and post-dam situations affects long-term aquatic life. Furthermore, a case study is conducted using the selected hydrological flow assessment methods, Tennant and Tessman methods, and comparisons are made. The calculated flows are compared with monthly average flow values before dam construction, projected environmental flow data, and the current situation. Accordingly, Tennant's good classification is proposed to determine the environmental flow (EF) for the considered case study.
Keywords: Environmental flow; Environmental flow assessment; Ecological flow; Hydropower plant; Energy sustainability; INSTREAM ECOLOGICAL FLOW; WETTED-PERIMETER; REQUIREMENTS; ENERGY; BASIN; OPERATION; IMPACTS; DAMS; Environmental Sciences & Ecology